Problematika Kelompok dalam Konseling - Marpaung, Alhudani; Syarqawi, Ahmad (IAI Nasional Laa Roiba Bogor, 2024)
The literature study method is a series of activities relating to methods of collecting library data, reading and taking notes, and managing research materials (Zed, 2008:3). Literature study is an activity that is required in research, especially academic research whose main aim is to develop theoretical aspects as well as aspects of practical benefits. Literature studies are carried out by each researcher with the main aim of finding a basis for obtaining and building a theoretical basis, framework of thinking, and determining temporary assumptions or also known as research hypotheses. So that researchers can grup, allocate, organize and use a variety of libraries in their field. By conducting literature studies, researchers have a broader and deeper understanding of the problem to be researched. The implementation of grup counseling services certainly does not go straight without any problems that follow. Along the way, there are various kinds of problems that follow the development of grup counseling services. In this research, the author will explain various grup problems in the implementation of counseling services.